Trichoadenoma of Nikolowski - Krishna Swaroop Duddi; Ramakrishna B; Bai Sarala; Shanthi V (Wolters Kluwer Medknow Publications, 2008)
Trichoadenoma of Nikolowski is a rare benign cutaneous tumor, which is usually solitary, nodular and occurs on the face or buttocks any time during adult life. The morphological differentiation of trichoadenoma is situated between a trichofolliculoma and a trichoepithelioma with hair follicle-like direction of differentiation. We report this case of trichoadenoma in a 28-year-old man who presented with a solitary nodular and ulcerated swelling in the gluteal region, gradually increasing in size. Excision biopsy revealed characteristic features consistent with trichoadenoma. We report this case in view of its rarity.